The Relations Between Muslim Community and Prostitution in Bandungan - Firhandika Ade Santury; Hendra Try Ardianto; Rachmad Gustomy (Universitas Sultan Ageng Tirtayasa, 2023)
This study aims to explain how the relationship between Muslim communities and prostitution is present in everyday social life, especially in the prostitution area of Bandungan, Semarang Regency. With the case study research method, the authors conducted observations, documentation, and structured and unstructured interviews simultaneously with prostitution business actors, Muslim associations, and local government actors. As for the findings, first, the relationship between society and prostitution has been socially shaped over a very long period, not something that appears instantly. The gradual social change from the colonial era to the emergence of tourism gave rise to the characteristics of prostitution, which were relatively different from the localization models of prostitution in other regions. Second, the relationship between the Muslim community and prostitution is intertwined in social relations because of intertwined economic interests. Third, social disharmony is still present despite social harmony, especially in the relations of citizens who do not depend on their economic interests in the prostitution business, especially among people who are affiliated with Muslim organizations. This study concludes that the relationship between the Muslim community and prostitution occurs dynamically, which is still contradictory but has no conflict with each other.